Мистецтво вітражу в архітектурі храмових споруд Львова періоду Ренесансу - Задорожний, Богдан; Zadorozhny, Bogdan (Видавництво Львівської політехніки, 2021)
У процесі дослідження вітражів в оздобленні ренесансних храмів та каплиць у Львові проаналізовано технологію виготовлення, композиційне рішення, їх колористичну гаму та виявлено основні особливості художньо-образного виразу.

The stained glass art of temples and chapels of the Renaissance period occupies a special place in the fine arts of Lviv. Special attention is drawn to the stained glass windows of Lviv's sacred buildings, which impress with their aesthetics, composition, colours, and artistic expressiveness. In the process of studying stained glass windows in the decoration of Renaissance churches and chapels in Lviv, the manufacturing technology, compositional solution, their colour scheme were analyzed and the main features of their artistic and figurative expression were revealed. Renaissance stained glass windows have not survived, all stained glass windows of Lviv temple buildings were made in the XIX – early XX centuries. The stained glass compositions of the Church of the Assumption are marked by a simple and at the same time refined composition and picturesque colours in light tones in contrast to the Gothic patterns. Ornamental stained glass compositions were used in the interiors of the chapels. Ukrainian artists of monumental art used the latest progressive technologies of making stained glass. Professional foreign artists - connoisseurs of stained glass art – were invited to make stained glass window compositions of Lviv Renaissance temple buildings. All stained glass windows of Lviv's sacred buildings are highly artistic decorative works and belong to Ukrainian artistic heritage.
The art of stained glass in the architecture of temple buildings of the Renaissance period in Lviv
Keywords: вітраж; композиція вітражу; колористичне вирішення; художньо-образний вираз; stained glass; stained glass composition; colour solution; artistic expression; 726. 71